PENGARUH PENGGUNAAN LARUTAN KUNYIT (Curcuma domestica Val) TERHADAP pH DAN ALT IKAN BELOSO (Glossogobius sp.) - Harmain, Rita Marsuci; Dali, Faiza A.; Kalaka, Sri Rahayu (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2024)
This study aims to determine the effect of using turmeric (Curcuma domestica Val) solution on the pH and ALT of beloso fish (Glossogobius sp.). The treatment factor is a turmeric solution consisting of 10% (A), 20% (B) and 30% (C) for soaking times of 12 hours, 24 hours, 36 hours and 48 hours. The data analysis used was a Completely Randomized Factorial Design and the data results were significantly different followed by the Least Significant Difference (BNT) test. The results of the research showed that the use of turmeric solution and different soaking times had an effect on the pH and ALT of beloso fish. Beloso fish soaked in 30% turmeric solution for 24 hours had a pH value of 5.72% and an ALT value of 3.2x105 colonies/g. These results are in accordance with SNI 01-2729.1.2006 concerning fresh fish.